Scaling Approach for Estimating Pore Connectivity Coefficient for Open Slit-Like Capillaries - Volodymyr V. Kutarov; Yuri I. Tarasevich; Eugene V. Aksenenko (Adsorption Science & Technology)
To estimate the pore connectivity coefficient for open slit-like capillaries, the qualitative and quantitative description of adsorption hysteresis based on the Frenkel–Halsey–Hill formalism is used. A scaling-related governing equation is derived that provides a generalized description of the desorption branch of the hysteresis loop. The proposed equation is shown to be capable for an adequate description of data for several experimental systems, which leads to reliable values of the pore connectivity coefficient.